A plea for a practical education - Curtis, Edwin McMaster Stanton (My University, 1893)
Introduction: As the world grows older, and its inhabitants wiser, the value of knowledge that is practical is more and more appreciated. In our advanced civilization, where a vast majority of the world’s artisans receive all the education they have crowded in the brief space of three year’s time, we can see the value of placing within that time those things that will be of the greatest value to the greatest number.
Citation: Curtis, Edwin McMaster Stanton. A plea for a practical education. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Knowledge; Education; Value; Theses; Manuscripts (documents)